The Effect of Various Two-wheeler Camshaft Materials on Dynamic Response Using Finite Element Analysis - Tira, Hendry Sakke; Dwilingga, Ikhsan (ROTASI, 2023)
A camshaft from a 4-stroke engine operating at idle with an average speed of 650 rpm was studied. The study was carried out using the finite element method and the Ansys software. The study was carried out to determine the dynamic response (reaction force, stress distribution, and deformation) of a camshaft circuit operating under torsional pressure at 650 rpm for 1 s. Analysis studies were carried out by varying the camshaft materials such as structural steel, aluminum alloy, and stainless steel. The results of this numeric study show that the structural steel camshaft has the greatest total deformation when compared to the other two materials. Stainless steel has the highest equivalent stress value, followed by structural steel, and aluminum alloy has the lowest. These findings also suggest that aluminum alloy has a better structural response than other materials. This is due to the aluminum alloy having the lowest stress of 239.87 MPa. This is supported by the relatively high safety factor value of 2.165, which is higher than the other two materials.